Fifty great contemporary thinkers : from structuralism to postmodernity - Lechte, John (Routledge, 2004)
Fifty Key Contemporary Thinkers surveys the most important figures who have influenced post-war thought. The reader is guided through structuralism, semiotics, post-Marxism and Annales history, on to modernity and postmodernity. With its comprehensive biographical and bibliographical information, this book provides a vital reference work of the last fifty years.